Train scheduling for minimizing passenger waiting time with time-dependent demand and skip-stop patterns: Nonlinear integer programming models with linear constraints - Niu, Huimin; Zhou, Xuesong; Gao, Ruhu (Transportation research. Part B: methodological, 2015)
•Optimization models for train scheduling problem for minimizing passenger waiting time.•Quadratic functional form for computing waiting time under time-dependent OD demand.•Reformulations for linking train inter-arrival events under skip-stop patterns.•Implemented and efficiently solved by general purpose high-level optimization solvers. This paper focuses on how to minimize the total passenger waiting time at stations by computing and adjusting train timetables for a rail corridor with given time-varying origin-to-destination passenger demand matrices. Given predetermined train skip-stop patterns, a unified quadratic integer programming model with linear constraints is developed to jointly synchronize effective passenger loading time windows and train arrival and departure times at each station. A set of quadratic and quasi-quadratic objective functions are proposed to precisely formulate the total waiting time under both minute-dependent demand and hour-dependent demand volumes from different origin–destination pairs. We construct mathematically rigorous and algorithmically tractable nonlinear mixed integer programming models for both real-time scheduling and medium-term planning applications. The proposed models are implemented using general purpose high-level optimization solvers, and the model effectiveness is further examined through numerical experiments of real-world rail train timetabling test cases.